Study on mechanism of down-regulating ikca1 molecule affecting the increment of oral squamous cell carcinoma - Liu, Jianmin; Guo, Ying (Cellular and Molecular Biology, 2020)
This research aimed to explore the mechanism of mediating the down-regulation of the calcium-activated potassium channel (IKCa1) gene expression in human oral squamous cell carcinoma Tca-8113 cells, thereby affecting cell proliferation and apoptosis. The expression level of IKCa1 in Tca-8113 cell line (oral squamous cell carcinoma) and HOEC cell line (human normal oral epithelial cell) was detected by RT-PCR. Then, after IKCa1 was knocked down in Tca-8113 cell line and HOEC cell line by RNA interference, and then cell proliferation levels were detected by cell counting kit 8 (CCK-8) method. Cell cycle distribution was detected by flow cytometry. Apoptosis was detected by membrane linked protein V-FITC/propidium iodide (PI) double-staining apoptosis detection kit. The protein expression level of IKCa1 was detected by Western Blot method. According to RT-PRC results, IKCa1 was significantly more expressed in Tca-8113 cell line than in HOEC cell line (P< 0.01). In addition, the mRNA expression levels in the normal oral epithelium and oral squamous cell carcinoma showed the same trend. After knocking down IKCa1 in Tca-8113 cell line, the IKCa1siRNA group significantly inhibited cell proliferation compared with the siNC control group. The results of flow cytometry showed that the proportion of apoptotic Tca-8113 cells transfected with IKCa1siRNA was significantly increased. The ratio of early apoptosis and late apoptosis of Tca-8113 cells increased (P< 0.05). To investigate the effect of IKCa1 on apoptosis, we tested the expression levels of apoptosis-related proteins. The results showed that the mRNA level of IKCa1siRNA group was significantly decreased by 44.41% compared with the control group (p< 0.01). Meanwhile, the mRNA level of Bax was significantly increased by 36.0% (p< 0.05). Our results showed that knocking down IKCa1 in Tca-8113 cells could induce cell cycle arrest and apoptosis to produce an anti-proliferation effect, thus inhibiting the expression of IKCa1 has an anti-cancer effect in oral squamous cell carcinoma.